Transformasi Strategis Pengembangan Sumber Daya Manusia di Era Digital: Sintesis Tantangan, Peluang, dan Agenda Masa Depan Depan - Ella Mayasari (MAMEN: Jurnal Manajemen, 2026)
The rapid development of digital technology has brought significant changes to the management and development of human resources (HR), making human resource development in the digital era an important topic for comprehensive study. This study aims to identify the challenges and opportunities of HR development in the digital era based on recent literature. The method employed is a literature review by examining national and international scholarly articles published between 2021 and 2025, sourced from Google Scholar, SINTA, and reputable academic journals. The findings indicate that the main challenges in HR development in the digital era include digital skill gaps, resistance to change, limitations in technological infrastructure, and organizational readiness to adopt digital-based HR management systems. Conversely, the digital era also offers significant opportunities, such as increased efficiency in HR management, enhancement of competencies through digital learning, implementation of upskilling and reskilling strategies, and the utilization of artificial intelligence in HR development. This review concludes that HR development in the digital era requires adaptive and sustainable strategies to enable organizations to enhance competitiveness and long-term sustainability amid rapid technological changes.